Frontiers in Nondrug Treatment of Sarcopenia: A Review of Pathological Mechanisms and the Latest Treatment Strategies - Qi‐Fei Kuang; Yu‐Qing Ni; You‐Shuo Liu (Aging Medicine)
ABSTRACT Sarcopenia refers to the progressive decline and wasting of skeletal muscle function, typically linked to aging or as a secondary effect of various conditions, including systemic inflammation, oxidative stress, and mitochondrial dysfunction. Recent scientific research underscores that skeletal muscle function is regulated by multiple factors. These include not only physical activity, environmental exposures, and genetic tendencies, but also nutritional deficiencies. Currently, pharmacological interventions for sarcopenia remain a matter of ongoing debate; the recommended strategies for promoting muscle health center on nutritional support therapy and physical exercise. This review offers an insightful examination of the molecular pathways and Pathophysiology contributing to skeletal muscle atrophy and highlights recent progress in employing nonpharmacological approaches (particularly, nutritional supplementation and physical exercise) for its prevention and management. To provide new scientific evidence and effective strategies for the prevention and treatment of sarcopenia, help to bolster the preservation of skeletal muscle function, and improve the quality of life and health of the elderly.